2000
DOI: 10.1007/s000560050011
|View full text |Cite
|
Sign up to set email alerts
|

Torquedrehmomentübertragung zwischen Vierkantdraht und Bracket als Funktion von Maß-, Form- und Härteparametern

Abstract: The aim of the study was to investigate the influence of cross section, edge geometry and structural hardness on torque transmission between square wire and bracket. For this purpose, 5 different brands of stainless steel square wire in 3 dimensions (0.016" x 0.016", 0.016" x 0.022" and 0.017" x 0.025") were inserted into edgewise brackets with a slot size of 0.018" and loaded with different torques (1 and 3 Ncm). The slot and wire geometries were analyzed by computer on ground specimens before and after loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Using the same formula, the difference between the average torque play between a Speed and Damon bracket is 2.3°. These torque play differences are an idealized estimate, and actual torque play is dependent on factors such as bracket/wire friction and beveling of wire corners [2, 11–13]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same formula, the difference between the average torque play between a Speed and Damon bracket is 2.3°. These torque play differences are an idealized estimate, and actual torque play is dependent on factors such as bracket/wire friction and beveling of wire corners [2, 11–13]. …”
Section: Resultsmentioning
confidence: 99%
“…Orthodontic bracket slot profile variances have an impact on torque play and third-order torque expression [2, 3]. Typically the bracket slot height will be stated as a nominal height; previous studies have found variations between the nominally stated sizes and the measured sizes [49], with some brands being oversized up to 27% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors that studied orthodontic materials developed mechanical devices to conduct their researches 8,19,20 . Others used computerized systems 7 or graphic computation systems (CAD) 14 . Nevertheless, optical microscopy was frequently involved 3,6,15,24,30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in spite of incorporating ideal torque characteristics in the structure of such brackets, in some cases it is necessary to apply additional or individual torques on some teeth. This would occur due to several factors 10,27 : mechanical side-effects 25 , morphological differences in the buccal faces of teeth 4,6,9,21,22,26 , changes in the position of the brackets 2,16,22,29 , different methods of bracket manufacturing 12,30 and orthodontic wires 24 , the play between the wire and the bracket slot 3,4,7,16,24,25 , variations in the bracket designs 8 , properties of the materials constituting the brackets 7,8,11,13,23 and wires 24 and differences between the value of the torque informed by the manufacturer and the real value of the torque of the brackets 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Accurately measuring and predicting torque expression and understanding the sources of losses are critical to providing predictable orthodontic treatment results. Several studies have measured in vitro torque expression using different devices and techniques looking at wire/bracket play, different brackets, and wire configurations, among other variables showing that torque expression was largely affected by these variables [25, 8, 1421]. …”
Section: Introductionmentioning
confidence: 99%